2021
DOI: 10.3389/fphar.2021.647084
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Species Difference of the Hepatotoxicity of Medicine Based on Transcriptome

Abstract: In recent years, several drugs have been withdrawn from use by regulatory bodies owing to hepatotoxicity; therefore, studies on drug-induced liver injury (DILI) are being actively pursued. Most studies evaluating DILI use rats or mice as animal models to determine drug toxicity; however, the toxicity of a drug can vary between rats or mice. These inconsistencies in in vivo studies among different animal models affect the extrapolation of experimental results to humans. Thus, it is particularly important to cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…In light of our findings, it is possible that this is due to the greater capacity of the rat liver to cope with the initial chemical insult and mitigate against the progression of downstream toxic events. Consistent with our findings, Xu et al 27 recently reported that mice better resemble humans in terms of the basal hepatic expression of oxidative stress-related genes, whilst rats better resemble humans in terms of the expression of genes associated with lipid metabolism. Transgenic Nrf2 null mice have been reported to exhibit greater susceptibility to a large number of liver toxins, including APAP 28 , whilst Kang et al 29 recently reported that the response of an Nrf2-associated gene set was typically higher in primary rat, compared with human, hepatocytes exposed to a large panel of liver toxic and safe drugs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In light of our findings, it is possible that this is due to the greater capacity of the rat liver to cope with the initial chemical insult and mitigate against the progression of downstream toxic events. Consistent with our findings, Xu et al 27 recently reported that mice better resemble humans in terms of the basal hepatic expression of oxidative stress-related genes, whilst rats better resemble humans in terms of the expression of genes associated with lipid metabolism. Transgenic Nrf2 null mice have been reported to exhibit greater susceptibility to a large number of liver toxins, including APAP 28 , whilst Kang et al 29 recently reported that the response of an Nrf2-associated gene set was typically higher in primary rat, compared with human, hepatocytes exposed to a large panel of liver toxic and safe drugs.…”
Section: Discussionsupporting
confidence: 93%
“…Our study highlights the higher basal and inducible activity of the Nrf2 antioxidant and autophagy stress responses in the livers of rats, compared with mice and humans. Consistent with our findings, Xu et al (39) reported that mice better resemble humans in terms of the basal hepatic expression of oxidative stress-related genes, whilst rats better resemble humans in terms of the expression of genes associated with lipid metabolism. Transgenic Nrf2 null mice have been reported to exhibit greater susceptibility to a large number of liver toxins, including APAP (40), whilst autophagy has been implicated in the pathogenesis of DILI (41) and shown to act as a defence mechanism in APAP hepatotoxicity by removing damaged mitochondria (42).…”
Section: Discussionsupporting
confidence: 93%
“…Case 1 developed a rash after taking an acetaminophen-containing Chinese patent medicine, developed severe liver function impairment 1 week later, and progressed to subacute liver failure 2 months later. Qubaibabuqi tablets were taken by Case 2, which contains the Chinese herb Psoralea that is known to induce oxidative stress that may cause DILI ( Xu et al, 2021 ). The patient progressed to ALF and hepatic encephalopathy after using the medicine for more than 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous in vitro tools that are largely implemented for the assessment of the hepatotoxic potential of various compounds and that offer a valid platform to investigate mechanisms of mitochondrial toxicity. Human-based models are preferred over animal-derived systems because of their better predictive and translational value [ 186 , 187 ]. However, both are used, especially since there is a low availability of human material.…”
Section: Experimental Models and Methods To Study Hepatic Mitochondri...mentioning
confidence: 99%